Applying the Darwin Core data standard to wildlife disease – advancements toward a new data model. Issue 11 (24th November 2022) - ,; Jaroszynska, Francesca; Body, Guillaume; Pamerlon, Sophie; Archambeau, Anne‐Sophie
Abstract: Wildlife diseases have an impact on biodiversity, economy, and public health. As this impact increases with climate change, land‐use change and trade, a multidisciplinary approach in analysing data from these different disciplines is increasingly required. The need for a common data standard to improve data sharing of surveillance efforts is thus larger than ever to enable transnational proactive and reactive measures to be taken. The Enetwild consortium, funded by the European Food and Safety Authority (EFSA), evaluated the capacity for the Darwin Core standard to handle wildlife disease data. In addition to two new terms previously proposed by Enetwild, the Darwin Core standard proved to have the flexibility to handle complex datasets from a wide variety of research and surveillance sources from local to international scales. Integration of the data model to the Global Biodiversity Information Facility is discussed, and controlled vocabularies specific to epidemiological data are proposed.